Quantitative oscillator analysis of IR-optical spectra on spin-cast chitosan films. Issue 5 (2005) - Nosal Nosal, W.H. W.H.; Thompson Thompson, D.W. D.W.; Sarkar Sarkar, S. S.; Subramanian Subramanian, A. A.; Woollam Woollam, J.A. J.A.
Abstract : Infrared optical properties of spin-cast chitosan films have been determined using spectroscopic ellipsometry. Infrared index of refraction and extinction coefficients from 750 cm –1 to 4000 cm –1 were determined using ellipsometric data fits to dispersion models based on Gaussian shaped oscillators. The free electron contribution was analyzed using a Drude model. This modeling determined that optical anisotropy was present over the entire infrared region. Line shape and oscillator strength analysis was performed to determine oscillator strengths, abundance, and relative bond strength.